Open-DO: Open Framework for Critical Systems - Ruiz, Jose; Comar, Cyrille (Electronic Communications of the EASST, 2009)
Critical systems development pushes software quality to the extreme. When human life depends on the correct operation of the software, strict processes are put in place to ensure, as much as possible, the absence of errors in the airborne system. These processes are very tool-demanding, and these tools also need to follow stringent and rigorous guidelines to provide the proper guarantees of quality. The Open-DO initiative aims at providing a framework federating open-source tools for safety-critical systems. A key point is that these tools will come with the material to ensure that industrial users can trust their output and use them to develop software compliant to the highest integrity levels.